Impact of Nutritional Insufficiency on Nutritional Status of Adolescents in low and high Income Socio Economic Group - Moha Akram Khan, Mahnaz Nasir Khan, Fasiha Ilyas, Memoona Khalid, Muhammad Abiodullah, M. Imran Hussain, S. S U Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Adolescence is the most crucial period with uplifted energy need that demands an intense nutritive care for fulfillment of complete good wellbeing in the upcoming life course and evaluation of the nutrient inadequacy as a part of their daily routine tells about diet quality which is an essential element at every stages of a human life. Aim: To assess the energy insufficiency of adolescents in low and high socioeconomic status as it has high significance in the growing stages because it affects both the physiological and psychological aspects of overall well-being. Method: This was a comparative cross-sectional study. The research was conducted on 410 adolescent girls and boys with age ranging from 10 to 14 years of Lahore from public and private sector schools selected through lottery method that basically reflects low and high socioeconomic background effects with detailed energy intake analysis and association of nutritional status to the total energy consumed per day of these groups. The data was collected on the basis of a questionnaire consisting of demographics and 24-hr recall calculated by taking an average of the last 3 days’ food intake. Results: The results revealed that adolescent groups belonging to high socioeconomic class were more in the normal health status, had less energy insufficient values and better food quality than adolescents from low socio economic class. Practical implication: The study will provide light to do in depth research should be conducted in the community in innovative ways for the better understanding of nutritional health related problems and its solutions for the children as well as adolescents as the new generation are the future of our beloved country. Conclusion: The result shows that as socioeconomic status tends to get better, diet quality improves and encourages a healthy lifestyle as compared to those living in improvised conditions. Keywords: Adolescence, Nutrient Inadequacy Energy Insufficient, 24-Hr Recall